2011
DOI: 10.3109/14767058.2011.589932
|View full text |Cite
|
Sign up to set email alerts
|

Maternal plasma concentrations of angiogenic/anti-angiogenic factors are of prognostic value in patients presenting to the obstetrical triage area with the suspicion of preeclampsia

Abstract: Objective To determine if maternal plasma concentrations of placental growth factor (PlGF), soluble endoglin (sEng), soluble vascular endothelial growth factor receptor-1 (sVEGFR-1) and -2 could identify patients at risk for developing preeclampsia (PE) requiring preterm delivery. Study design Patients presenting with the diagnosis ‘rule out PE’ to the obstetrical triage area of our hospital at <37 weeks of gestation (n=87) were included in this study. Delivery outcomes were used to classify patients into 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
104
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(125 citation statements)
references
References 162 publications
13
104
0
3
Order By: Relevance
“…Early confirmation of preeclampsia is particularly useful in patients who present very prematurely, in whom accurate diagnosis is critical for management. In this regard, 2 recent studies demonstrated not only that the measurement of angiogenic factors is useful in the triage setting for diagnosing preeclampsia, but also that it may be useful for the identification of patients at risk for adverse outcomes and preterm delivery (83,84 ).…”
Section: Clinical Relevance Of Preeclampsia Prediction and Diagnosismentioning
confidence: 99%
“…Early confirmation of preeclampsia is particularly useful in patients who present very prematurely, in whom accurate diagnosis is critical for management. In this regard, 2 recent studies demonstrated not only that the measurement of angiogenic factors is useful in the triage setting for diagnosing preeclampsia, but also that it may be useful for the identification of patients at risk for adverse outcomes and preterm delivery (83,84 ).…”
Section: Clinical Relevance Of Preeclampsia Prediction and Diagnosismentioning
confidence: 99%
“…Plasma concentrations of the angiogenic factor, placental growth factor (PlGF), are decreased [69,70,92,93,96,[100][101][102], and the anti-angiogenic factors (soluble vascular endothelial growth factor receptor-1 [sVEGFR-1] and soluble endoglin [sEng]) are elevated both prior to [67,72,[119][120][121][122][123][124][125] and at the time of diagnosis [94,95,[97][98][99]. Moreover, the concentrations of these factors can be used to predict the outcome of the disease in patients presented to the obstetrical triage area [73,75,126,127]. However, the prognostic performance of these biomarkers evaluated in the mid-trimester for late-onset preeclampsia has been suboptimal [105,[128][129][130][131].…”
Section: Introductionmentioning
confidence: 99%
“…Considerable effort has been made to identify biomarkers that could predict women who will develop preeclampsia [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. Although markers of systemic inflammation [79,80] and endothelial dysfunction [81][82][83][84][85][86][87][88] in maternal blood have been associated with preeclampsia, their prognostic performance for the identification of patients with preeclampsia prior to diagnosis has been disappointing [79][80][81]83,[89][90][91].…”
Section: Introductionmentioning
confidence: 99%
“…This simple, quantitative, rapid test outperformed the standard battery of clinical diagnostic measures including blood pressure, proteinuria, uric acid, and other laboratory assays 57 . Importantly, sFlt1 and/or PlGF levels at presentation were strongly associated with the remaining duration of pregnancy 53,[57][58][59][60] . We also recently evaluated the role of sEng measurements and found that it has comparable performance to sFlt1/PlGF ratio 61 .…”
Section: Clinical Implications For Diagnosis and Treatment Of Preeclamentioning
confidence: 99%